Experience and level of confidence in the management of dental trauma among dental students and fresh graduate dentists - Favour Osasenaga Ikhile; Enabulele Emien Joan (Wolters Kluwer Medknow Publications, 2024)
Background Dental trauma is one of the most serious and frequent oral problems in active children as well as adolescents worldwide. Anyone can be a victim. Hence, the level of competence in the management cannot be undermined. Aim This study aims to evaluate the experience and confidence in the management of dental trauma among dental students and fresh graduate dentists in Benin City, Nigeria. Methodology This questionnaire-based, analytical, and cross-sectional study utilized a self-administered questionnaire containing 15 closed- and open-ended questions to garner data from respondents. Data from 95 respondents were analyzed using the Statistical Package for the Social Studies software version 26.0 (IBM Corporation, Chicago, Illinois, USA.), and both univariate and bivariate analyses were used in this study. Results A substantial proportion of respondents 73 (76.8%) had never managed any case of dental trauma. A relatively higher proportion of respondents were more confident in managing cases of enamel fracture 18 (18.9%), enamel infraction 17 (17.9%), and enamel-dentine fracture 12 (12.6%) as compared to other more complicated fractures. Conclusion The experience and level of confidence in the management of dental trauma among dental students and fresh graduate dentists were found to be poor, and they were more confident in managing less complicated cases of dental trauma.